Indoor air mycoflora of residential dwellings in Jos metropolis - Ayanbimpe, GM (Makerere Medical School, 2010)
BACKGROUND: The quality of air in the environment where one lives or works can have potential effects on human health. There are strong indications that in many parts of the world, our homes, schools and workplaces are heavily contaminated with air-borne molds and other biological contaminants. OBJECTIVES: This study was carried out to assess the level of fungal contamination of indoor air, health related experiences of residents, and the prevalent fungi species in the homes. METHODS: The investigation was done between May 2005 and January 2006, using structured questionnaires and the agar plate exposure. 150 houses from 14 locations were examined. RESULTS: 380 fungi belonging to 10 species were isolated, Chaetomium globosum (17%), Aspergillus fumigatus (14%), Stachybotrys alternans (14%) and Alternaria alternata (14%) being the predominant isolates. CONCLUSION: The indoor air quality of residential dwellings in Jos is poor. Rate of isolation of fungi was not significantly different in the wet and dry periods of the year and residential density affected the occurrence of fungal contaminants. Residents are displeased with fungal presence in their homes and the associated health implications. There is need for proper attention to the quality of the indoor environment.